CULTURE OF TOLERANCE IN THE NATIONAL SPIRITUALITY OF UZBEKISTAN - Malikov Turdali Toshmirzaevich (Western European Studies, 2025)
This article argues that it is a methodological problem to focus on the contradiction between traditional and modern in the analysis of tolerance in national spirituality, because globalization and the development of information technology allow our society to penetrate the achievements of world culture. Tolerance is an indicator of a democratic culture, a principle of human rights and freedoms formed at the stage of industrial development based on the rule of law.
Keywords: National ideology; national spirituality; norms of tolerance